Elementos para a formulação de uma psicossomática psicanalítica - Maniakas, Georgina Carolina Oliveira Faneco (2008)
From the link between the works of Freud, Ferenczi and Groddeck, this study attempts to show that psychoanalysis, since their first developments, provides evidence for the formulation of a psychoanalytic psychosomatic. In the first chapter, when we approach psychoanalytic concepts that are in the intersection between the psychic and somatic, we present evidences suggesting that somatic changes that affect somatic functions and/or structures are produced when, under impact of a traumatic situation, added by the insufficiency of the specific action, the discharge of the affection occurs of a totally unconscious way, running a cumulative excitement that found no other way of expression. This means of discharge, which is based upon the acting, not on the word, can come up from phylogenesis after the failure of the ontogenesis to equip the individual with more consistent reactions to him face limit-situations of reality. Prevented from acting against the object, the natural aggressiveness -inherent to the instincts of preservation of the species- acts in the way to disrupt the psychic functioning or, if it is sufficiently protected by the cleavage of the ego, disorganizing the somatic structures. On that regression beyond the psychic limits, selfdestructiveness, remnant of the original masochism, expressed a force even more basic in the formation of living being, as sought to show in the second chapter. Identified by Freud at both the psychological level as in the somatic level, the death drive extends the roots of unconscious to the biological level, considering the existence of an undifferentiated region between soma and psyche, where the variations of a level impact on the other. This hypothesis is supported: (1) by Ferenczi, who introduced changes in analytical technique with the aim of promoting a regression able to access content from traumatic experiences, and reached archaic and undifferentiated contents, that remains detained in the body as a memory without words, at the margin of language and the further development of the ego, producing psychical and somatic suffering, (2) by the location of the It at the psychic apparatus, connected directly with the somatic forces. By tracing the origin of It until the thought of Groddeck, in the third chapter, we find an unconscious-It that precedes the psychosomatic existence. For Groddeck, the lack of symbolic significance of organic diseases are due to the split between soma and psyche inherent at the explanatory model, for which the disease and the sickness organs are not seen as symbols that can be decoded and resized from the symbolic nature of unconscious. Finally, we show that, in despite the work of Freud provides explanations for the psychosomatic phenomenon in a psychoanalytic perspective it is Groddeck and Ferenczi that provide the clinical features that allow rescuing the psychosomatic phenomenon to become synonymous with lack of symbolization. Despite Freud have remained away of this issue and skeptical about the resolution of the psychosomatic disease through analysis, some of his assertions in his last years show that the creator of metapsychology not remained totally unrelated to that possibility.